Normative ethics - Kagan, Shelly. 1956-
"Providing a thorough introduction to current philosophical views on morality, Normative Ethics examines an act's rightness or wrongness in light of such factors as consequences, harm, and consent. Shelly Kagan offers the actual working practices of contemporary moral philosophers. The first of the book presents a systematic survey of the basic normative factors, focusing on controversial questions concerning the precise content of each factor, its scope and significance, and its relationship to other factors. The second half of the book then examines the competing theories abaut the foundations of normative ethics, theories that attempt to explain why the basic normative factors have the moral significance that they do...."